Night in Shanghai - Mones, Nicole (Houghton Mifflin Harcourt, 2014)
"Sailing to Shanghai in 1936 to lead a black jazz orchestra, Thomas Greene goes from being flat broke in segregated Baltimore to living in a mansion with servants of his own, and from the classical piano pieces he was trained to play to the toe-tapping swing of the big band era. Song Yuhua is refined, educated, and bonded since age eighteen to Shanghai's most powerful crime boss in payment for her father's gambling debts. Outwardly submissive, she burns with rage, longs for escape, and risks her life spying on her master for the Communist Party. With Shanghai shattered by the Japanese invasion, Thomas and Song find their way to each other and forge a bond from which neither can back down in the turbulent years that follow. Torn between music and survival, freedom and commitment, love and war, they navigate the dangers leading to world war until the moment when they must cast their lots in Night in Shanghai's final, impossible choice. "--